Assessment of agricultural sustainability in Pakistan - Zulfiqar, Farhad; Thapa, Gopal B.; Shivakot, Ganesh P.; Soparth Pongquan; Higher Education Commission (HEC),Pakistan; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2013)
The research is about the assessment of the agricultural sustainability in Pakistan at the provincial level.Main objectives of the research are to analyze sustainability of agriculture at provincial level from economic, social and environmental perspective based on selected indicators, and to make province specific policy recommendations for promotion of socioeconomically and environmentally sustainable agriculture.This research study was carried out to assess the status of agricultural sustainability from year 2005-06 to 2010-11. Province specific policy recommendations were proposed to improve the socioeconomic and environmental sustainability of agriculture in Punjab, Sindh, KPK and Balochistan. The data analysis was performed in order to find out the sustainability of the agriculture at the provincial level based on economic, social and environmental determinants. For the purpose of comparison the year 2005-06 was taken as base year similar to the norm adopted by the government of Pakistan. The data for all the indicators was analyzed from the year 2005-06 to 2010-11 or for the latest available data. This was because the last agricultural census in Pakistan, which provides comprehensive information on most of the agricultural variables, was carried out in 2010. The data was collected from the secondary sources and quantitative data analysis techniques were employed. This research found out that the three dimensions of sustainability rank the provinces differently. While Sindh and Punjab province fared impressively in economic and social sustainability aspect of agricultural sustainability, their performance on the environmental front was disappointing, pointing towards needs to improve on this aspect. On the other hand KPK and Balochistan displayed a poor show on socioeconomic aspects while at the same time showing good performance on the environmental dimension of agricultural sustainability. In conclusion, there was need to progress for the improvement of agricultural sustainability in all four provinces albeit on different fronts. For the enhancement of agricultural sustainability at the provincial level certain recommendations were put forward. These mainly focused on province specific policies because of different socioeconomic and biophysical conditions prevailing in provinces.
A research submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Research studies project report (M. Sc.) - Asian Institute of Technology, 2013
Keywords: Sustainable agriculture -- Pakistan